INTEGRATION OF MEDICINE AND DIFFERENT DISCIPLINES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The article discusses the integration of medicine and science. History of medicine, description of medicinal properties of medical works. New science networks and achievements were analyzed as a result of the integration of medicine and linguistics, medicine and music, medicine and literature, medicine and history, medicine and pedagogy. Theoretical and practical aspects of the development of music therapy, poetry therapy, medical and pedagogical education as a result of the communication of medicine and the sciences are discovered.